Regulatory Science And Social Movements: The Trial Against The Use Of Agrochemicals In Ituzaingó. - Arancibia, Florencia Paula (2016)
In August 2012 a transgenic soy producer and a pesticide spraying pilot were sentenced to three years of conditional prison for potential pollution and harm to public health in Cordoba, Argentina. This was the first case of pesticide pollution judged by Criminal Law in Latin America and the verdict became a turning point in the struggle to regulate pesticides in Argentina. The trial was initiated by the movement “Madres de Ituzaingó” from a neighborhood surrounded by transgenic soy fields sprayed with glyphosate-based herbicides (to which GM seeds are resistant). They found an increase in cancer rates and made the nexus between their illnesses and glyphosate exposure. In this way, they challenged official “regulatory science”, which classifies glyphosate as a product of low toxicity, commercialized and used without restriction. Through in-depth interviews and ethnographic observation, I found that the ruling was an outcome of interconnected actions which included typical forms of protest, the production of “undone science”, as well as other actions involving expertise.